STRUCTURE OF THE PRIPYAT PALEORIFT AT DEPTH - Garetskiy R.G.; Klushin S.V. (My University, 1987)
Reflection shooting in the modified form of deep seismic sounding by the common-depth-point method (DSS-CDP) has recently been increasingly employed to study the structure of the crust and upper mantle. DSS-CDP surveys were run along certain profiles crossing the Pripyat trough submeridionally and continuing onto the Ukrainian shield and the Belorussian anteclise, respectively. Each profile was about 2000 km long. It is found that the main factor controlling the development of the Pripyat palerofit was a system of listric surfaces, penetrating down to the M-discontinuity and into the crust-mantle mixture zone. The latter could be a cluster of thrust sheets, generated at the crust-mantle junction. Under the paleorift, the lithosphere was reworked as a result of extension and the rise of an asthenospheric lens, as expressed in the appearance of clinoforms at the base of the crust on shoulders of the trough. Thus, the authors data confirm the concept of structural layering of the lithosphere that recognize the contribution of physicochemical inhomogeneities.